Nonverbal Communication in Clinician-Patient Interaction and Influence on Healthcare Outcome - Ekole, Alphonse (American Journal of Trade and Policy, 2022)
Communication is essential during clinicians’ patient encounters in determining the health outcome. The importance of nonverbal communication has received less attention in the patient direct care model, both in practice and healthcare communication. This is because of the nature of the approach itself. Our goal was to investigate the impact nonverbal communication research conducted during the last quarter century has had on various health outcomes. Body language is a powerful tool that may help healthcare providers connect with patients and build mutual respect. In the context of medical encounters, this research aims to provide a summary of the previous research that has been conducted on nonverbal communication. After giving the roles of nonverbal behavior and its importance in medicine, we show how physician nonverbal conduct relates to patient pleasure, trust, or adherence. We then present nonverbal behavior assessment tools. Finally, it has been determined whether or not interpersonal sensitivity affects patient outcomes.